Financial Analysis of Litchi (Litchi chinensis Sonn.) Production in Dinajpur District of Bangladesh (The Agriculturists, 2017)
The present study was conducted in 2015 to examine the profitability of litchi orchard production at Dinajpur sadar upzila in Dinajpur district where litchi orchards are generally leases out for 1 to 6 years by the owners known as Deed. In total 312 litchi orchard trees of which 254 were Bombai, 40 Madrazi, 20 China-3, 2 China-2 and 3 were Bedana, were selected to estimate the BCR, NVP and IRR of litchi production. The litchi trees were 18 to 22 years old. Project appraisal techniques and sensitivity analysis was done by using primary data to determine cost and benefits from litchi production. The study revealed that individuals investment on litchi production is profitable. The study also found that in producing litchi Benefit Cost Ratio (BCR), Net Present Value (NPV) and Internal Rate of Return (IRR) were 1.93, Tk. 1643896 and Tk. 1230, respectively. Sensitivity analysis suggested that the investment in litchi production is profitable even for 10% increase in operating and maintenance cost or 10% decrease in gross benefit.The Agriculturists 2016; 14(2) 32-37